Implementation of the Pancasila Student Profile Strengthening Project in Improving Students' Understanding of Democracy in Junior High School - Nisa Aliza Trigina; Wingkolatin; Nur Fitri Handayani; Novita Majid (South Sulawesi Education Development (SSED), 2025)
Education has a strategic role in developing students' potential, both cognitively, skills, and attitudes, one of which is realized through the implementation of the Independent Curriculum with the Pancasila Student Profile Strengthening Project (P5). This study intends to: (1) find out the implementation of P5 in improving students' understanding of democracy at SMP Negeri 11 Samarinda, (2) identify supporting and inhibiting factors for the implementation of P5 related to democracy education, and (3) formulate solutions to overcome obstacles that arise. Qualitative descriptive research is the approach implemented in this study, where data is collected by implementing semi-structured interview techniques, field observation, and documentation. The research informants consisted of PPKn teachers, P5 coaching teachers, and students who were active in project activities. The results of the study show that the implementation of P5 with the theme